2016
DOI: 10.1097/qai.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Age-Discordant Partnerships Associated With HIV Risk Among Young South African Women (HPTN 068)

Abstract: Objective Sexual liaisons between older men and younger women have been linked to greater risk of HIV acquisition. This study aims to: 1) identify psychosocial and behavioral factors associated with age-discordant (partner ≥ 5 years older) versus age-concordant partnerships (−1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
(37 reference statements)
3
13
0
Order By: Relevance
“…Disclosing HIV status to a partner (whether a negative, positive or unknown status) was less likely to happen when that partner was an adolescent girl, ages 15–19 years, versus older (ages 20+ years), as well as when that partner was more than five years younger than the respondent. This concurs with recent findings of attributes of age disparity in relationships that are directly responsible for placing young women at risk—including more frequent sex and less consistent condom use [ 5 , 27 ], and further suggests that conversations about HIV status may be particularly difficult in relationships with adolescent girls specifically. However, few studies report on (or perhaps measure) HIV status disclosure, which the present findings suggest may be an important factor to assess and address.…”
Section: Discussionsupporting
confidence: 90%
“…Disclosing HIV status to a partner (whether a negative, positive or unknown status) was less likely to happen when that partner was an adolescent girl, ages 15–19 years, versus older (ages 20+ years), as well as when that partner was more than five years younger than the respondent. This concurs with recent findings of attributes of age disparity in relationships that are directly responsible for placing young women at risk—including more frequent sex and less consistent condom use [ 5 , 27 ], and further suggests that conversations about HIV status may be particularly difficult in relationships with adolescent girls specifically. However, few studies report on (or perhaps measure) HIV status disclosure, which the present findings suggest may be an important factor to assess and address.…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiologic studies of relationships and contraceptive use have demonstrated a strong association between relationship type, and contraceptive decision-making including condom use [26]. For example, evidence shows that condom use is negotiable when the age range between partners is within 5 years, and this has been linked to gender-power dynamics [26,[29][30][31][32]. The results also showed that contraceptive use was less likely among AGYW who had not given birth as observed in other studies [33].…”
Section: Discussionmentioning
confidence: 62%
“…While similar associations between age-disparate relationships and condom use [ 18 22 ] or sex frequency [ 20 , 21 ] have been noted in other studies, the relationship between age differences and duration of relationships has been less studied. We found that the older a man was compared to the girl, the less likely they were to terminate their relationship.…”
Section: Discussionmentioning
confidence: 81%
“…Second, older male partners are more likely to be in a concurrent relationship [ 7 , 13 , 17 ], which increases the likelihood young women will be sexually active with a man when he experiences acute HIV infection. Finally, age-asymmetric relationships have been reported to result in inconsistent condom use [ 18 22 ] and higher frequencies of sex [ 20 , 21 ]. This could be due to the gender-power imbalances that may be more likely in age-disparate relationships, and which result in less ability of younger women to negotiate when and how sex occurs [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%